Spy ski school : the graphic novel - Gibbs, Stuart, 1969- (Gibbs, Stuart, 1969- Spy school the graphic novel (Series), 2025)
Thirteen-year-old Ben Ripley's unexpected success outside the classroom causes the CIA to activate him for a mission to become friends with Jessica Shang, daughter of a suspected Chinese crime boss.